Structural change in the British economy, 1948-1968 - Armstrong, Alan.; Stone, Richard (Edinburgh : Published for the Department of Applied Economics, University of Cambridge by Chapman & Hall ; New York : distributed by Halsted Press, 1974)
This study is mainly the work of Alan Armstrong, who left Cambridge at the end of 1969 to take up an appointment at the University of Bristol. The aim of the project is to study quantitatively in as great details as possible the present structure and future prospects of the British economy, the possibilities of stimulating its rate of growth and the problems to which this would give rise.
Includes bibliographical references: p. 163-169.
osc 07/01/2019
Loans
Keywords: Gross national product; National income